Intra-articular corticosteroids versus intra-articular corticosteroids plus methotrexate in oligoarticular juvenile idiopathic arthritis: a multicentre, prospective, randomised, open-label trial. - Ravelli, Angelo; Davì, Sergio; Bracciolini, Giulia; Pistorio, Angela; Consolaro, Alessandro; van Dijkhuizen, Evert Hendrik Pieter; Lattanzi, Bianca; Filocamo, Giovanni; Verazza, Sara; Gerloni, Valeria; Gattinara, Maurizio; Pontikaki, Irene; et al. (Lancet, 2017)
BACKGROUND: Little evidence-based information is available to guide the treatment of oligoarticular juvenile idiopathic arthritis. We aimed to investigate whether oral methotrexate increases the efficacy of intra-articular corticosteroid therapy. METHODS: We did this prospective, open-label, randomised trial at ten hospitals in Italy. Using a concealed computer-generated list, children younger than 18 years with oligoarticular-onset disease were randomly assigned (1:1) to intra-articular corticosteroids alone or in combination with oral methotrexate (15 mg/m; maximum 20 mg). Corticosteroids used were triamcinolone hexacetonide (shoulder, elbow, wrist, knee, and tibiotalar joints) or methylprednisolone acetate (ie, subtalar and tarsal joints). We did not mask patients or investigators to treatment assignments. Our primary outcome was the proportion of patients in the intention-to-treat population who had remission of arthritis in all injected joints at 12 months. This trial is registered with European Union Clinical Trials Register, EudraCT number 2008-006741-70. FINDINGS: Between July 7, 2009, and March 31, 2013, we screened 226 participants and randomly assigned 102 to intra-articular corticosteroids alone and 105 to intra-articular corticosteroids plus methotrexate. 33 (32%) patients assigned to intra-articular corticosteroids alone and 39 (37%) assigned to intra-articular corticosteroids and methotrexate therapy had remission of arthritis in all injected joints (p=0·48). Adverse events were recorded for 20 (17%) patients who received methotrexate, which led to permanent treatment discontinuation in two patients (one due to increased liver transaminases and one due to gastrointestinal discomfort). No patient had a serious adverse event. INTERPRETATION: Concomitant administration of methotrexate did not augment the effectiveness of intra-articular corticosteroid therapy. Future studies are needed to define the optimal therapeutic strategies for oligoarticular juvenile idiopathic arthritis. FUNDING: Italian Agency of Drug Evaluation.
Keywords: Adrenal Cortex Hormones; Arthritis, Juvenile; Humans; Injections, Intra-Articular; Italy; Methotrexate; Prospective Studies; Treatment Outcome

EULAR/PRINTO/PRES criteria for Henoch-Schönlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part I: Overall methodology and clinical characterisation. - Ruperto, Nicolino; Ozen, Seza; Pistorio, Angela; Dolezalova, Pavla; Brogan, Paul; Cabral, David A; Cuttica, Ruben; Khubchandani, Raju; Lovell, Daniel J; O'Neil, Kathleen M; Quartier, Pierre; Ravelli, Angelo; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To report methodology and overall clinical, laboratory and radiographic characteristics for Henoch-Schönlein purpura (HSP), childhood polyarteritis nodosa (c-PAN), c-Wegener granulomatosis (c-WG) and c-Takayasu arteritis (c-TA) classification criteria. METHODS: The preliminary Vienna 2005 consensus conference, which proposed preliminary criteria for paediatric vasculitides, was followed by a EULAR/PRINTO/PRES - supported validation project divided into three main steps. Step 1: retrospective/prospective web-data collection for HSP, c-PAN, c-WG and c-TA, with age at diagnosis <or=18 years. Step 2: blinded classification by consensus panel of a subgroup of 280 cases (128 difficult cases, 152 randomly selected) enabling expert diagnostic verification. Step 3: Ankara 2008 Consensus Conference and statistical evaluation (sensitivity, specificity, area under the curve, kappa-agreement) using as 'gold standard' the final consensus classification or original treating physician diagnosis. RESULTS: A total of 1183/1398 (85%) samples collected were available for analysis: 827 HSP, 150 c-PAN, 60 c-WG, 87 c-TA and 59 c-other. Prevalence, signs/symptoms, laboratory, biopsy and imaging reports were consistent with the clinical picture of the four c-vasculitides. A representative subgroup of 280 patients was blinded to the treating physician diagnosis and classified by a consensus panel, with a kappa-agreement of 0.96 for HSP (95% CI 0.84 to 1), 0.88 for c-WG (95% CI 0.76 to 0.99), 0.84 for c-TA (95% CI 0.73 to 0.96) and 0.73 for c-PAN (95% CI 0.62 to 0.84), with an overall kappa of 0.79 (95% CI 0.73 to 0.84). CONCLUSION: EULAR/PRINTO/PRES propose validated classification criteria for HSP, c-PAN, c-WG and c-TA, with substantial/almost perfect agreement with the final consensus classification or original treating physician diagnosis.
Keywords: Adolescent; Biopsy; Child; Delphi Technique; Granulomatosis with Polyangiitis; Humans; International Cooperation; Internet; Polyarteritis Nodosa; Purpura, Schoenlein-Henoch; Reproducibility of Results; Takayasu Arteritis